Reformulation of the editorial project of the Magazine Informação na Sociedade Contemporânea (Research, Society and Development, 2021)
This paper presents suggestions for the process of reformulation of the editorial project of the Information Society in Contemporary Society (RISC), a scientific journal linked to the Department of Information Science (DECIN) and the Post-Graduation Program in Information and Knowledge Management of the Federal University of Rio Grande do Norte (UFRN). In order to determine the elements that the project should contain and which policy should be presented to be a development channel in this type of publication, compare RISC's editorial policies and processes with those of other leading journals in the area of Information Science , identifying and indicating good editorial practices for them to be applied in the RISC. The comparative analysis will take place with the magazines: Informação & Sociedade, Perspectivas em Ciência da Informação and Transinformação.